Antipredator mechanisms displayed by Gymnodactylus darwinii (Squamata: Phyllodactylidae) and Chatogekko amazonicus (Squamata: Sphaerodactylidae) when handled in fieldworks - Bruno Becacici Loureiro; Thiago Silva-Soares; Waltécio de Oliveira Almeida; Fabrício Oda (Revista de Biologia Neotropical, 2022)
Brazil is one of the richest countries in reptile fauna. However, the antipredator mechanisms regarding many of these species are not yet known. As we document new records, it may continually improve our understanding on predator-prey interactions. Here, four antipredator mechanisms are reported, the scorpion mimicry displayed by Gymnodactylus darwinii and Chatogekko amazonicus, as well as cloacal discharge, skin loss, and tail autotomy for the former.